Consumer-Driven Growth: Analyzing the Relationship Between Brand Loyalty and Consumer Behavior in the Ice Cream and Tea Industry - Gan Kia Hui; Lay Hong Tan; Qi Zhang; Jia Hui Zhang; Shu Kun Zhang; Ke Xian Zhao; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
As the economy grows and quality of life improves, there is a noticeable uptick in beverage consumption among people. Amidst numerous milk tea brands, MIXUE Ice Cream Tea distinguishes itself with its prudent capital management, swiftly expanding its market across various regions of China and overseas. This study aims to delve into the relationships between different aspects of consumer behavior (preferences, purchase intention, service experiences) and brand loyalty towards MIXUE Ice Cream Tea, providing valuable insights for enhancing customer retention and brand competitiveness. The findings suggest that perceived quality, promotions, brand services, and consumer preferences have little to no significant impact on brand loyalty, highlighting that the other factors, like affordability and customer engagement, maybe more influential. These results challenge traditional views and imply that MIXUE should adopt a balanced approach to brand strategy, focusing on deeper customer connections rather than solely relying on quality or pricing strategies. Additionally, this study endeavors to offer valuable insights for other players in the tea industry, potentially shaping their operational strategies and contributing to the overall market development.